Carol Rama and the Pleasure of Image - Ivanova, Eva-Maria (Sledva : NBU Journal of Humanities and Arts, 2020)
Carol Rama is one of the most provocative artists of the XX and XXI centuries. Although in different periods her work has been associated with some of the significant artistic movements of the XX century, such as surrealism, art brut, arte povera, she does not join any of the leading trends and artistic groups. This makes her work a challenge to the history of contemporary art.